KAJIAN MOTIVASI DALAM UPAYA PENCAPAIAN TUJUAN PROGRAM PERTUKARAN PEMUDA INDONESIA-KANADA 2014-2015 - Made Panji Teguh Santoso (Eqien - Jurnal Ekonomi dan Bisnis, 2017)
Youths are the hope and determining achievement factors of a country’s future success. International youth exchange program, in this case Indonesia-Canada Youth Exchange Program (ICYEP) 2014-2015, has been one of the options taken by the two countries. Motivations of young people to join ICYEP 2014-2015 are strongly related to the achievement of ICYEP 2014-2015 objectives. Douglas McGregor’s Theory Y and Daniel Pink’s Self-Determination Theory can be used to explain their motivations. ICYEP 2014-2015 provides ways for its participants to achieve their motivations. The motivations, in turns, ends in the achievement of the objectives of ICYEP 2014-2015 having been outlined by the Ministry of Youth and Sport of the Republic of Indonesia (Kemenpora RI) and Canada World Youth (CWY). Utilizing qualitative method, this research aims to identify participants’ motivations to participate in ICYEP 2014-2015, achievements, constraints, and relations to the accomplishment of the objectives of ICYEP 2014-2015. The research results display that there are various kinds of motivations supporting research subjects’ decisions to participate in ICYEP 2014-2015, and this program provides the right paths to attain their motivations. There are correlations between the achievement of research subjects’ motivations and the accomplishment of ICYEP 2014-2015. Keywords: motivations, Indonesia, Canada, youth exchange program, objectives.